Character resistance as a compliance of homosexual desires in Elisa y Marcela movie by Isabel Coixet: a Slavoj Å½iÅ¾ek’s psychoanalysis-historical approach - Faradilla, Dhitya (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2023)
The purpose of this study was to reveal the movement of Elisa and Marcela in their movement to fulfill their desire as a lesbian couple contained in the film Elisa Y Marcela by Isabel Coixet. This study uses Slavoj Å¾iÅ¾ek’s theory about the subject to understand the character’s subjectivity in dealing with symbolic dimensions that ensnare him and how to escape the symbolic reality. This research is included in the Descriptive Qualitative study, in which data is presented as words sourced from the Elisa Y Marcela film script. Data collection is done by watching movies repeatedly, understanding the film to be analyzed, and collecting data following research problems. Data analysis techniques include observation, textual analysis, and conclusion. The main focus of this study is on the figures of Elisa and Marcela. The results of this study show that Elisa and Marcela, as the main characters succeeded in knocking down symbolic in their lives. They do not care about people’s thoughts of similar relations they run, Elisa and Marcela remain together and do not give up. Both of them know that their relationship is wrong and forbidden, but they continue, calling them cynical subjects. After all the rejection they received, they finally tried to make lies, and one of them disguised as men, and their actions indicated a moment of emptiness when the subject had reached the disgust of all that trapped him. In the end, they carried out radical acts, they had a marriage in the church legally, made lies to the priest in the church, and lied to many people. Thus, they can both fight the symbolic with these radical actions.